Nazwy własne w przekładzie. Zarys problematyki - Wolnicz-Pawłowska, Ewa (Poznańskie Spotkania Językoznawcze, 2014)
The article briefly presents the history of the absorption of foreign proper names by the Polish language. The introduction outlines the key properties that differentiate proper names from common names. Then the three chief periods in the history of Polish are presented, along with their typical, dominant ways of absorbing proper names. These periods coincide with the periodization proposed by Z. Klemensiewicz (Old-Polish, Middle-Polish, New-Polish periods). The author discusses finally the main modes of absorbing proper names: phonetic-morphologic adaptation (e.g. Piotr, Agnieszka, Szymbark), adideation and reinterpretation (e.g. Bakchus – Beczkoś), translation (e.g. Felix – Szczęsny, Parva – Mała), transposition (e.g. Milano, Trier, Inez).